Kinemy w Kabarecie - Hendrykowski, Marek (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
There’s more to discover about Bob Fosse’s masterpiece Cabaret (1972) through these two inspiring shots. Marek Hendrykowski’s comprehensive study including detailed in-depth analysis of the opening and last shot of Berlin 1931 story enlarges the scope of understanding of film poetics used in Cabaret. It also demonstrates the crucial importance of the outstanding direction, filming and editing to that unique film.
Kinems in Cabaret